Inheritance Sharing Expert System - Subianto, Muhamad Elvin; Rafdhi, Faiz (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
One of the computer-based information systems is a website, usually this web information system is in offline or online form. Dissemination or delivery of information carried out on online information systems can be accessed by anyone and anywhere with the provision that they must have an internet connection. The purpose of this study is to provide a solution through the study of several theories and observations in the design of a web-based inheritance distribution expert system. The author uses the forward chaining method in designing an expert system. The application development methodology that I use is the ESDLC (Expert System Develop Life Cycle) method. The expected result of this research is the creation of an application design that can simplify the process of calculating inheritance in accordance with Islamic perspective because inheritance is often crucial which sometimes triggers disputes and causes rifts in family relationships and crime. Therefore we need an expert system that can assist in performing calculations.